Analisis Peran Sarana dan Prasarana dalam Proses Pendidikan Jasmani dan Keolahragaan di Sekolah Dasar - Fajar Sidik Siregar; Riska Sri Pratiwi Tambunan; Febri Deasari Simamora; Delima Situmorang; Karina Sitorus (Lembaga Pengembangan Kinerja Dosen, 2024)
The background of this study is based on the importance of adequate facilities to support the effectiveness of learning, where many schools still face challenges in terms of the availability and quality of sports facilities. This study aims to analyze the role of facilities and infrastructure in the process of physical education and sports in elementary schools. This study uses a qualitative method with data collection techniques sourced from literature reviews sourced from books, journals and other scientific documents to gain an in-depth understanding of the condition of existing facilities and infrastructure and their impact on physical education learning. The results of the study indicate that good facilities and infrastructure contribute positively to student involvement in physical activity, while lack of facilities can hinder the learning process and reduce student interest.